Efektivitas Pemberian Sari Kacang Hijau terhadap Anemia pada Ibu Hamil - Juli Astutik, Tri; Susanti, Komaria; Rahayu, Ary Oktora Sri; Aifa, Wira Ekdeni (Sinar : Jurnal Kebidanan, 2026)
Background:  Consumption of green bean juice is one of the non-pharmacological treatments that can be done to increase hemoglobin levels in pregnant women. Purpose: This study aims to determine the effectiveness of giving mung bean juice to increase hemoglobin levels in pregnant women. Methods: This type of research is quantitative research with a one group pretest-posttest design. The samples in this study were 18 pregnant women with anemia. The sampling technique is purposive sampling, results of data normality testing using the Wilcoxon test. Results: The results showed that before the intervention, all respondents (100%) had anemia with an average hemoglobin level of 10.072 g/dL. After the intervention, the number of respondents with anemia decreased to 72.2% and 27.8% were not anemic, with an average hemoglobin level increasing to 10.678 g/dL. The Wilcoxon test results showed a p value = 0.000 (p < 0.05), which means there was a significant difference between hemoglobin levels before and after the intervention. Conclusion:  Green bean juice can be an alternative to increase hemoglobin levels, as an alternative non-pharmacological intervention in the management of anemia during pregnancy in primary health care